2014
DOI: 10.1161/circgenetics.113.000451
|View full text |Cite
|
Sign up to set email alerts
|

G Protein–Coupled Receptor Kinase 5 Gene Polymorphisms Are Associated With Postoperative Atrial Fibrillation After Coronary Artery Bypass Grafting in Patients Receiving β-Blockers

Abstract: Background We hypothesized that genetic variations in the adrenergic signaling pathway and cytochrome P450 (CYP) 2D6 enzyme are associated with new-onset atrial fibrillation (AF) in patients who underwent coronary artery bypass graft (CABG) surgery and were treated with perioperative beta-blocker (BB). Methods and Results Two cohorts of patients who underwent CABG surgery and received perioperative BBs at Duke University Medical Center were studied. In a discovery cohort of 563 individuals from the Periopera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
30
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 25 publications
(32 citation statements)
references
References 48 publications
(74 reference statements)
1
30
0
1
Order By: Relevance
“…In our recent candidate gene study, we found an association between variants of G protein-coupled receptor kinase 5 ( GRK5 ) gene polymorphisms and postoperative AF in the discovery and replication datasets from a subset of patients who exclusively received perioperative beta-blocker therapy. 15 In the current larger dataset, this association was still present in our discovery dataset (Supplemental Table 5), but did not reach our discovery threshold of P < 5 × 10 −5 that was required for replication in the CATHGEN cohort. This may be due to the fact that in the current study, we expanded our study cohorts to include patients with and without perioperative beta-blocker therapy.…”
Section: Discussionmentioning
confidence: 61%
See 1 more Smart Citation
“…In our recent candidate gene study, we found an association between variants of G protein-coupled receptor kinase 5 ( GRK5 ) gene polymorphisms and postoperative AF in the discovery and replication datasets from a subset of patients who exclusively received perioperative beta-blocker therapy. 15 In the current larger dataset, this association was still present in our discovery dataset (Supplemental Table 5), but did not reach our discovery threshold of P < 5 × 10 −5 that was required for replication in the CATHGEN cohort. This may be due to the fact that in the current study, we expanded our study cohorts to include patients with and without perioperative beta-blocker therapy.…”
Section: Discussionmentioning
confidence: 61%
“…15 Briefly, 1004 samples from the PEGASUS cohort (discovery samples) were genotyped using the Illumina Human610-Quad BeadChip.Various QC criteria were applied to ensure the genotype quality. Markers were excluded if the GenCall (http://support.illumina.com/downloads/gencall_software.html) score was ≤ 0.15, the genotype call frequency was < 98%, or gender errors were detected At the sample level, we checked cryptic relatedness and duplications.…”
Section: Methodsmentioning
confidence: 99%
“…The parent PEGASUS study enrolled 1004 patients who underwent isolated non-emergent CABG surgery with cardiopulmonary bypass (CPB) between 1997 and 2006 [10]. The iPEGASUS study enrolled 1159 patients to study the effects of cardiothoracic surgery on the proteome, gene expression, and metabolic profile of patients undergoing cardiothoracic surgery between 2004 and 2011 using blood, plasma, and tissue from the perioperative genomics biorepositories stored in the Duke Department of Anesthesiology, Durham, North Carolina.…”
Section: Methodsmentioning
confidence: 99%
“…We recently demonstrated that genetic variation in the G protein-coupled receptor kinase 5 gene ( GRK5 ) is associated with postoperative AF in patients who underwent CABG surgery and were treated with BBs perioperatively [10]. Unfortunately, this genetic association study could not provide insight into the potential pathophysiological mechanisms associated with postoperative AF in patients treated with BBs.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation